University Quality Management System (Appreciations y Reflections) - Ibañez Machicao, Mario (2017)
We talked so much about the reality of peruvian university system and, we see that in the last thirty years with more of three university laws with its complements and modifications were publishes, all of them, only for the political or economical powers of interests with the fact that, today, the peruvian university is completely merchantilized or marketing bussines. Its why, today we have public, private and managerial university. We suggest a new Peruvian educational system and, a way to orient the new peruvian educational and university quality management system.